Pengembangan Billing Online Sistem dengan Menggunakan Metode Rapid Application Development - Harsih Rianto; Omar Pahlevi (STMIK Budi Darma, 2022)
Billing management system and services at PT. Media Prima Jaringan is still not properly and efficiently recorded. Data management and recording still uses manual processes and paper media so that errors can occur in calculating Customer Service bills. So that customer complaints often occur due to inappropriate bill values, late payments until service termination occurs. In addition to complaints, company customers will also experience losses from dissatisfied customers who switch to other providers because they stop subscribing to the service. With the development of an online billing system, it is hoped that it will make it easier for companies to manage invoices and customer data and avoid billing errors. In developing a system, systematic steps are needed to produce a good and quality information system that can be used by users. The fundamental stages in the System Development Life Cycle (SDLC) are the planning stage, the analysis stage, the design stage, the implementation stage, the testing stage and the maintenance stage. One of the SDLC development models is Rapid Application Development (RAD) which prioritizes a relatively short development time of around 60-90 days. In addition to using the RAD model for system development, the author also uses the Unified Modeling Language (UML) as a tool in the design stage. The programming language used to build this information system uses PHP (Hypertext Pre-processor) by implementing the Laravel framework and MySQL as the database. The implementation of the RAD method for the development of an online billing system takes 45 days of development. The intensity of the discussions that were carried out during development helped the programmer team complete the program design more quickly. The increase in company revenue increases after the system is running and customer complaints are also reduced.